2021
DOI: 10.1044/2021_aja-21-00021
|View full text |Cite
|
Sign up to set email alerts
|

Listening in 2020: A Survey of Adults' Experiences With Pandemic-Related Disruptions

Abstract: Purpose The COVID-19 pandemic has introduced lifestyle changes that may negatively impact communication, including the pervasive use of face masks and videoconferencing technology. Here, we examine the effects of age and self-rated hearing on subjective measures of speech understanding via a survey accessed by adults residing in the United States. Method Responses to an online survey were obtained from adults (21 years of age and older) during the summe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…However, the effect of this age difference on the outcomes is presumed to be minimal. A previous large survey of 1,700 people showed that the age of the listener did not affect the degree of communication disturbance caused by masks (Helfer et al, 2021). Moreover, ANCOVA was used to control for the age difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the effect of this age difference on the outcomes is presumed to be minimal. A previous large survey of 1,700 people showed that the age of the listener did not affect the degree of communication disturbance caused by masks (Helfer et al, 2021). Moreover, ANCOVA was used to control for the age difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the widespread use of masks causes inconvenience in everyday conversation. Many previous studies have confirmed that mask-wearing interferes with communication not only in hearing-impaired individuals, but also in individuals with normal hearing (Atcherson et al, 2017;Chodosh et al, 2020;Helfer et al, 2021;Rahne et al, 2021;Thibodeau et al, 2021). Listeners recalled significantly fewer words when the sentences were spoken with a face mask, because when speech delivered with a face mask is processed, fewer cognitive resources are available for storing speech in memory (Truong and Weber, 2021).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…31 An alternative (or complementary) explanation could again be age-related changes, here affecting hearing function (presbycusis). [32][33][34] The finding of significantly better performance on the verbal (letter) fluency task in the LPA cohort tested remotely compared with the cohort tested face-to-face is surprising. The obvious explanation is that the remote cohort was overall less impaired than the patients seen face-to-face; although efforts were made to match the two cohorts for disease severity and other potentially relevant factors.…”
Section: Open Accessmentioning
confidence: 98%
“…This is potentially consistent with the controls' preserved performance on the bisyllabic single word repetition test where top-down information can be used to complement bottom-up auditory information partially degraded by the videoconferencing software 49 . An alternative (or complementary) explanation could again be age-related changes, here affecting hearing function (presbycusis) [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%